The Effect of Exercise on Alcohol Use Disorders - Georgakouli Καλλιόπη; Manthou Ειρήνη; Fatouros Ιωάννης Γ.; Zourbanos Νίκος; Theodorakis Γιάννης; Gianoulakis, Christina; Jamurtas Αθανάσιος (Inquiries in Physical Education and Sport, 2016)
Alcohol use disorders are a major cause of death worldwide, and clinical management of them is of eminent importance. To date various programs applied for the treatment of alcohol use disorders have not been sufficiently effective. Consequently, research has turned into alternative coping strategies of these disorders, including exercise. Various psychological and physiological mechanisms triggered by exercise may also lead to reduced alcohol consumption. Research in this field is limited; however, there seems to be a relationship between exercise, endogenous opioid system and alcohol. This relationship supports the view that exercise could potentially be a substitute for alcohol consumption in individuals with alcohol use disorders.